Crisis Management in Tourism: Applied Psychological Strategies for Resilience and Recovery - Damiasih, D. (Golden Ratio of Data in Summary, 2025)
This study investigates crisis management in the tourism industry, focusing on psychological perspectives, stakeholder collaboration, and governance mechanisms. Utilizing a qualitative literature review approach, the research aims to explore the strategies, challenges, and implications of crisis management practices within tourism. The methodology involves comprehensive literature search, data collection, and analysis of key themes and patterns. Results reveal the significant impact of psychological factors such as emotions, perceptions, and coping mechanisms on tourists' responses to crises. Moreover, stakeholder collaboration and inclusive governance are identified as crucial for developing proactive crisis management plans and fostering resilience within tourism destinations. Findings highlight the importance of cultural competence, social support networks, and adaptive governance structures in enhancing crisis preparedness and recovery. Overall, the study contributes to theory-building and knowledge advancement in crisis management in tourism, emphasizing the need for integrating psychological perspectives and stakeholder collaboration into crisis management frameworks.